Gamma knife thalamotomy for essential and Parkinson’s tremor - Radžiūnas , A.; Laucius , O.; Kudrevičius , L.; Sėdžius , P.; Čelpačenko , I. (Neurologijos seminarai, 2021)
Background. The study aims to evaluate the efficacy of gamma knife thalamotomy for the control of essential tremor and Parkinson’s-related tremor when other invasive treatment modalities are not recommended.Materials and methods. From June 2019 to January 2021, 27 patients with medically resistant essential tremor and 20 patients with Parkinson’s disease (PD) underwent unilateral gamma knife thalamotomy. The patients were treated with a mounted Leksell G frame with modified 4 mm shots aiming to deliver 130-140 Gy to the ventralis intermedius nucleus. Post-surgical evaluation was to be performed 6 and 12 months after surgery. However, due to state-imposed quarantine restrictions direct evaluation was challenging, hence post-surgical results were evaluated via phone call. Only 12 of 20 PD patients were reached via phone call, but 8 of them were evaluated less than 6 months after surgery. As a result, the group of PD patients was excluded from the study.Results. 23 patients from the essential tremor group were assessed via phone call. One patient died from COVID-19-related pneumonia during the follow-up period. During the phone call, 16 (72%) of 22 patients reported major improvement in hand tremor or full tremor arrest on the contralateral side of thalamotomy. Meanwhile, 6 (28%) patients did not feel any improvement after the treatment. Complications were observed in 4 (18%) patients – they reported transient ataxia and hand movement dyscoordination which resolved in few months.Conclusions. Gamma knife thalamotomy is safe and effective for essential hand tremor control. Main disadvantages include several months of latency period and transient ataxia.
Keywords: gamma knife; thalamotomy; essential tremor; Parkinson’s disease